Decision Support System Prototype for Dispatch Personnel Based on CIM-standards and Modern IT-technologies; AIP Conference Proceedings; Vol. 2212 : Thermophysical Basis of Energy Technologies (TBET 2019) - Prutik A. F. Alexey Fedorovich (2020, 2020)
Title screen